MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA MELALUI MODEL PROBLEM-BASED LEARNING PADA MATERI BILANGAN PECAHAN - Khardiyawan A. Y. Pauweni; Moh. Efendi B. Iskandar (Universitas Negeri Gorontalo, 2020)
This study aims to improve students’ mathematical problem-solving ability through the Problem-Based Learning Model in Fractions learning material at grade VII of Junior High School SMP Negeri 10 Gorontalo. This classroom action research (CAR) involved 25 students as the subject and were conducted collaboratively between the researcher and teachers. This research was carried out in two cycles, and the first and second cycle consisted of three meetings, respectively. The instruments applied were an observation sheet of the teacher’s ability to manage the Problem-Based Learning Model, the observation sheet of students’ activity using the model above, and the ability tests to solve mathematical problems in the Fraction material. Further, the data were collected from observation and written tests. The results show an enhancement of the teacher’s ability in managing the Problem-Based Learning model and students’ activity using this model and the outcomes of mathematical problem-solving skill in the fractions learning material from cycle I to cycle II. Therefore, this finding indicates that the Problem-Based Learning model can be accepted as an alternative in learning Fractions at the research site.